Morphological evidence for the conspecific status of the rediscovered Mimulicalyx rosulatus and M. paludigenus - Zhao, Fei; Min, Dao-Zhang; Xiang, Chun-Lei; Chen, Bin; Zhou, Xin-Xin; Liu, Bing; Li, Bo (Phytotaxa, 2021)
Mimulicalyx is an oligotypic genus including two species that are endemic to southwest China. Based on investigation of the rediscovered populations of M. rosulatus and M. paludigenus, examination of their herbarium specimens (including types), as well as consultation of their protologues and distributions, no obvious morphological differences could be found and we thus concluded that they are conspecific. Therefore, M. paludigenus is reduced as a synonym of M. rosulatus. Field photographs and an updated morphological description of M. rosulatus are provided.